2019
DOI: 10.1111/1750-3841.14720
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Peptide Fractions Isolated from Wheat Germ Protein with Subcritical Water Extraction and Its Transport Across Caco‐2 Cells

Abstract: Wheat germ protein (WGP) was extracted with subcritical water and then hydrolyzed with Alcalase 2.4 L to obtain antioxidant hydrolysates. Wheat germ peptides (WG‐P, Mw < 1 kDa) were purified by using Sephadex G‐15 column chromatography. The results showed that WG‐P‐4 possessed the strongest DPPH radical scavenging activity in comparison with other peptides fractions. In addition, free amino acids and LC‐MS/MS analysis showed that Gly‐Pro‐Phe, Gly‐Pro‐Glu, and Phe‐Gly‐Glu were the major peptides of WG‐P‐4. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The Pepsin-Pancreatin system is commonly used to simulate GI digestion in vitro, which is often used to evaluate the stability of PAs in GI [232]. The experiment of the Caco-2 cell model demonstrated that the transmembrane transport mode of wheat germ peptide (Mw < 1 kDa) is mainly passive transport, which can exert an effective antioxidant effect through intestinal epithelium [233]. Three different cases of hydrophobic casein peptides were sequentially processed through simulated GI digestion and Caco-2 cell model, and the peptide nitrogen was used to evaluate the bioavailability (BA) and remaining peptide content [234].…”
Section: In Vitro Biological Evaluationmentioning
confidence: 99%
“…The Pepsin-Pancreatin system is commonly used to simulate GI digestion in vitro, which is often used to evaluate the stability of PAs in GI [232]. The experiment of the Caco-2 cell model demonstrated that the transmembrane transport mode of wheat germ peptide (Mw < 1 kDa) is mainly passive transport, which can exert an effective antioxidant effect through intestinal epithelium [233]. Three different cases of hydrophobic casein peptides were sequentially processed through simulated GI digestion and Caco-2 cell model, and the peptide nitrogen was used to evaluate the bioavailability (BA) and remaining peptide content [234].…”
Section: In Vitro Biological Evaluationmentioning
confidence: 99%
“…Small peptides have great potential application in antioxidant activity. Previous studies showed that small peptides from wheat germ protein and egg white protein also had good antioxidant activity (Chen et al., 2012; Zhang et al., 2019).…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Authors conclude that the elimination of unwanted metabolites, such as lipids and phenolic compounds, improved the degree of hydrolysis and antioxidant activity of quinoa protein hydrolysates ( Olivera-Montenegro, Best, & Gil-Saldarriaga, 2021 ). Similarly, Zhang et al (2019) extracted wheat germ protein with subcritical water, which was later enzymatically hydrolyzed with alcalase, obtaining small peptides (<1 kDa) with antioxidant activity.…”
Section: Conventional Approaches For Generation Identification and Va...mentioning
confidence: 99%